Calendula officinalis and Echinacae purpurae as antimicrobial agent - G., Jyotisree; R., Sruthi; Biju, C. R.; Menon, Amita S. (Journal of Applied Pharmaceutical Research, 2020)
Microorganisms includes viruses, bacteria, protozoan, fungi and algae. The potential sources of microbes includes soil, water, atmosphere, plants, animals etc., of which, soil is the No. 1 concern for microbes. They mainly cause infections in respiratory tract, gastro intestinal tract, urogenital tract, skin etc. The repeated intake of antibiotics against these infections leads to many adverse effects like antimicrobial resistance, which creates an urge for the society to depend on medicinal plants. Homeopathic medicine is considered as a complementary systems of medicine, which uses lower doses of plants, animals and inorganic substances to cure ailments and many of these homeopathic tinctures possess antimicrobial activity. This article reviews on antimicrobial property of Calendula officinalis and Echinacae purpurae mother tinctures and concludes that these two tinctures can be regarded as promising antimicrobial agents as they contain some phytochemical constituents responsible for the prevention of microbial growth